Efektifitas Pelatihan Kader dalam Meningkatkan Pengetahuan, Sikap dan Keterampilan Kader Mayangsari: Effectiveness of Training Cadres in Improving the Knowledge, Attitudes, and Skills of Mayangsari Cadres - Wiwik Khabibah Fitriani; Nani Surtinah; Nurwening Tyas Wisnu (Gema Bidan Indonesia, 2021)
The Maternal Mortality Rate in Magetan Regency in 2018 increased by 157.08/100,000 compared to 2017 at 97.57 / 100,000 live births. The increase in the number of high-risk pregnancies in 2018, which amounted to 24.60% also contributed to the high MMR in Magetan District. Based on the findings above, Magetan Regency has implemented the MAYANGSARII by cadres. This study aims to determine the effectiveness of cadre training in improving the knowledge, attitudes, and skills of MAYANGSARII. In this study, the type was analytic with a pre-experimental design in the form of a One Group Pre-Post Test design with a population of 50 cadres of PKK IV. Samples are taken with the total population. The instrument collects data on knowledge and attitudes using a questionnaire while the skills to use the checklist. The results of the study were analyzed by descriptive univariate in the form of mean, median, mode, and standard deviation and bivariate with Paired Samples T-Test. The results of the study showed that the average value of cadres' knowledge, attitudes, and skills after training increased. From the results of hypothesis testing the variable knowledge, attitudes, and skills obtained a value of p = 0,000. The conclusion of this study is that cadre training is effective in increasing the knowledge, attitudes, and skills of MAYANG cadres. It is recommended that the Magetan District Health Office continue to train MAYANGSARII cadres as a form of community empowerment in an effort to reduce AKI and AKB in the Magetan district.